Study of morphologic response of chondrocytes to uniaxial compression of articular cartilage - Wu, Ping; Kirk, Brett; Milne, N.; Delaney, P. (ACTA Press, 2008)
Osteoarthritis is synonymous to the functional disorder of articular cartilage. Mechanical tests of articular cartilage offer a way to understand the tissue’s functionality and osteoarthritis. During normal activities, chondrocytes (cells) are indirectly exposed to varied mechanical compressions exerted on articular cartilage. Study of the morphological response of chondrocytes to the mechanical compressions exerted on articular cartilage offers understanding the physical integrity of chondrocytes, and initial physiological change of articular cartilage for detecting early osteoarthritis. Fibre optic confocal microscopy uses fibre optic imaging technologies to study the internal microstructure of bulk articular cartilage. The technologies have led to develop confocal arthroscopy for in vivo studying the cellular structure of articular cartilage. Using fibre optic laser confocal microscopy and a developed computer image analysis software, we studied the morphological response of the chondrocytes in the superficial and transitional zone to the uniaxial compression of articular cartilage at 0.25MPa and 0.5MPa. The results suggest that the mechanical compression exerted on articular cartilage caused morphological changes of the chondrocytes, which can be measured by the technique described in this study. The technique developed in this study shows potential to develop a methodology for in vivo studying the physiological integrity of chondrocyte and early osteoarthritis.